Pendampingan Manajemen Pemasaran Produk Olahan Anggota PKK Desa Bangle Kec. Lengkong Kab. Nganjuk - Ali Anwar, Muhamad; Soim, Soim; Zakariya, Mukhamad; Subekan (Ngaliman: Jurnal Pengabdian Kepada Masyarakat, 2022)
Marketing is one of the fundamental activities that need to be carried out by business actors, marketing activities include planning, pricing, promotion and distribution of goods or services that satisfy the needs of both existing and potential buyers. So that the marketing of "bangle chips" managed by PKK members is absolutely necessary, and cooperation from business people, government and academics is needed. This assistance uses the CBR (Community Based Research) method. The result of this assistance is Peratama, there is a formal distribution permit for the product "bangle chips". PKK members can market to a wider audience. And its products can be trusted by consumers. Second, PKK members have marketing management knowledge and skills. After the training and mentoring, now they not only know marketing management, but already have a systematic and very technical marketing planning and organization. Third, increasing sales volume, currently marketing is carried out with three strategies, namely, leaving it at the souvenir center, through social media and selling directly to consumers. So that the market share is even wider, and according to the recognition of the PKK chairman there is an increase in the number of sales.